Sport tactical knowledge of primary school students - Serra-Olivares, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2014)
The purpose of this research was to analyze tactical knowledge (declarative and procedural) in Primary School students (156 boys and 132 girls aged 8-13 years). Students completed the Soccer Tactical Knowledge Test, and were analyzed depending on age, experience and gender. Significant differences were observed in tactical knowledge depending on age of the students (F= 8.490, p<.01, η2= .13), and gender (F= 135 853, p<.01, η2= .32). Likewise, hours of weekly practice and years of competition correlated significantly with tactical knowledge, (r= .46) and (r= .49) respectively. However, these correlations, as well as the effect size analysis suggested that these variables would not have been the primary cause of the differences observed. Therefore, further studies are needed to analyze the relationship between tactical knowledge and other factors such as formal instruction or the methodologies used in sport teaching.